An evaluative study to determine to what extent technology can be used in e-dictionaries to provide relevant information on demand - Bothma, T.J.D. (Theodorus Jan Daniel) (University of Pretoria, 2017)
Dissertation (MIS)--University of Pretoria, 2016.